Determinants of antibody persistence across doses and continents after single-dose rVSV-ZEBOV vaccination for Ebola virus disease: an observational cohort study. Issue 7 (July 2018) - Huttner, Angela; Agnandji, Selidji Todagbe; Combescure, Christophe; Fernandes, José F; Bache, Emmanuel Bache; Kabwende, Lumeka; Ndungu, Francis Maina; Brosnahan, Jessica; Monath, Thomas P; Lemaître, Barbara; Grillet, Stéphane; Botto, Miriam; et al.
Summary: Background: The recombinant vesicular stomatitis virus (rVSV) vaccine expressing the Zaire Ebola virus (ZEBOV) glycoprotein is efficacious in the weeks following single-dose injection, but duration of immunity is unknown. We aimed to assess antibody persistence at 1 and 2 years in volunteers who received single-dose rVSV-ZEBOV in three previous trials. Methods: In this observational cohort study, we prospectively followed-up participants from the African and European phase 1 rVSV-ZEBOV trials, who were vaccinated once in 2014–15 with 300 000 (low dose) or 10–50 million (high dose) plaque-forming units (pfu) of rVSV-ZEBOV vaccine to assess ZEBOV glycoprotein (IgG) antibody persistence. The primary outcome was ZEBOV glycoprotein-specific IgG geometric mean concentrations (GMCs) measured yearly by ELISA compared with 1 month (ie, 28 days) after immunisation. We report GMCs up to 2 years (Geneva, Switzerland, including neutralising antibodies up to 6 months) and 1 year (Lambaréné, Gabon; Kilifi, Kenya) after vaccination and factors associated with higher antibody persistence beyond 6 months, according to multivariable analyses. Trials and the observational study were registered atClinicalTrials.gov (Geneva:NCT02287480 andNCT02933931 ; Kilifi:NCT02296983 ) and the Pan-African Clinical Trials Registry (Lambaréné PACTR201411000919191). Findings: Of 217 vaccinees from the original studies (102 from the Geneva study, 75 from the Lambaréné study, and 40 from the Kilifi study), 197 returned and provided samples at 1 year (95 from the Geneva study, 63 from the Lambaréné, and 39 from the Kilifi study) and 90 at 2 years (all from the Geneva study). In the Geneva group, 44 (100%) of 44 participants who had been given a high dose (ie, 10–50 million pfu) of vaccine and who were seropositive at day 28 remained seropositive at 2 years, whereas 33 (89%) of 37 who had been given the low dose (ie, 300 000 pfu) remained seropositive for 2 years (p=0·042). In participants who had received a high dose, ZEBOV glycoprotein IgG GMCs decreased significantly between their peak (at 1–3 months) and month 6 after vaccination in Geneva (p<0·0001) and Lambaréné (p=0·0298) but not in Kilifi (p=0·5833) and subsequently remained stable at all sites apart from Geneva, where GMC in those given a high dose of vaccine increased significantly between 6 months and 1 year (p=0·0264). Antibody persistence was similar at 1 year and at 6 months in those who had received a low dose of vaccine, with lower titres among participants from the Geneva study at 2 years than at 1 year after vaccination (GMC ratio 0·61, 95% CI 0·49–0·77; p<0·0001). In multivariable analyses, predictors of increased IgG GMCs beyond 6 months included high-dose versus low-dose vaccination (Geneva p=0·0133; Lambaréné p=0·008) and vaccine-related arthritis (p=0·0176), but not sex, age, or baseline seropositivity (all p>0·05). Neutralising antibodies seem to be less durable, with seropositivity dropping from 64–71% at 28 days to 27–31% at 6 months in participants from the Geneva study. Interpretation: Antibody responses to single-dose rVSV-ZEBOV vaccination are sustained across dose ranges and settings, a key criterion in countries where booster vaccinations would be impractical. Funding: The Wellcome Trust and Innovative Medicines Initiative 2 Joint Undertaking.